Template Synthesis, Characterization and Biological Activity of Macrocyclic Transition Metal Complexes - Goel1, Vanita; Malhotra1, Rajesh (Asian Journal of Chemistry, 2016)
A novel macrocyclic transition metals complexes MLX2 [M = Co(II), Ni(II), Cu(II) or Zn(II); X = NO3–, Cl–, CH3COO–; L= condensation product of 1,3-dibenzoyl benzene and 1,8-diaminonaphthlene/1,4-diaminobutane] have been prepared by template method. These complexes were characterized by spectrochemical techniques (IR, NMR), molar conductivity, magnetic moment measurements, electronic spectral data, elemental analysis, ESR and TGA studies. Their biological activities expressed in terms of MIC have been explored for Gram-positive bacteria (Bacillus subtilis, Staphylococcus aureus), Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa) and phytopathogenic fungi (Candida albicans, Saccharomyces cerevisiae) and compared with the standard (ciprofloxacin, amphotericine-B).